A taxonomic review of the genus Rhinoceros with emphasis on the distinction of Eurhinoceros (Perissodactyla, Rhinocerotidae) - Francesco Nardelli; Kurt Heißig (ZooKeys)
This study examines the ecomorphological characteristics of two Asian rhinoceros species: the critically endangered Sundaic rhinoceros and the vulnerable Indian rhinoceros. Among the five living rhinoceros taxa, the three Asian species are notable for their tusked incisors. Fossil evidence highlights the divergence between Rhinoceros and Eurhinoceros in cheek tooth morphology, linked to different dietary specialisations. The Sundaic rhinoceros, a generalist browser restricted to the Ujung Kulon peninsula of Java, exhibits distinctive features such as a grey hide with polygonal patterns, a typical 'saddle' on the nape, a slender head shape and a protrusion instead of a horn in females. The latter is a unique trait among Rhinocerotini species. In contrast, the Indian rhinoceros, a variable grazer, inhabits riverine grasslands in northern India and southern Nepal, displaying deep skin folds and tubercles. Ecological behaviours differ significantly, with the Sundaic rhinoceros being solitary wanderers and Indian rhinoceros forming temporary crashes. Both species possess unique adaptations for survival, emphasising the importance of understanding their systematics for effective conservation. The study further examines the interrelationships among the one-horned Asian species of the Rhinocerotidae family, highlighting their distinct features. The revision delves into skull morphology, dentition, and ecological dynamics, revealing evolutionary patterns and ancestral traits. Both single horned rhinoceroses went a separate and diverging way of evolution that was not triggered by geographical separation but by niche partitioning. Comparative analyses shed light on the evolutionary trajectory and ecological adaptations of each species. The fossils, the ecological and morphological adaptations of both species, suggest designating 'Rhinoceros' sondaicus as distinct from Rhinoceros unicornis, under the one-horned rhinoceros Eurhinoceros, as proposed by Gray (1868). Eurhinoceros sondaicus emerges as a persistently more primitive form.